(untitled) (International Journal of Engineering and Computer Science, 2016)
: This paper deals with the concept of Optical Character Recognition (OCR) and its various stages like pre-processing, segmentation, feature extraction, classification and post-processing. The main objective of this paper is: • To study the existing techniques for recognition of handwritten Hindi text. • To develop and apply the new segmentation technique on the handwritten Hindi text collected from different users. . • To design a new feature set for the handwritten Hindi text. • Recognition of handwritten Hindi text.